2016
DOI: 10.29333/ojcmt/2556
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Review: Website Design and User Engagement

Abstract: Proper design has become a critical element needed to engage website and mobile application users. However, little research has been conducted to define the specific elements used in effective website and mobile application design. We attempt to review and consolidate research on effective design and to define a short list of elements frequently used in research. The design elements mentioned most frequently in the reviewed literature were navigation, graphical representation, organization, content utility, pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(105 citation statements)
references
References 8 publications
1
84
0
8
Order By: Relevance
“…The literature showed that various factors are associated as the antecedents and outcome of user engagement. In [5] identified 20 design elements that have an effect on user engagement: 1) organization; 2) content utility; 3) navigation; 4) graphical representation; 5) purpose; 6) memorable elements; 7) valid links; 8) simplicity; 9) impartiality; 10) credibility; 11) consistency/reliability; 12) accuracy; 14) security/privacy; 15) interactive; 16) strong user control capabilities; 17) readability; 18) efficiency; 19) scannability; and 20) learnability. However, out of the 20 design elements, seven were most often discussed in relation to user engagement, which is navigation, graphical representation, organization, content utility, purpose, simplicity, and readability.…”
Section: Literature Review and Research Modelmentioning
confidence: 99%
“…The literature showed that various factors are associated as the antecedents and outcome of user engagement. In [5] identified 20 design elements that have an effect on user engagement: 1) organization; 2) content utility; 3) navigation; 4) graphical representation; 5) purpose; 6) memorable elements; 7) valid links; 8) simplicity; 9) impartiality; 10) credibility; 11) consistency/reliability; 12) accuracy; 14) security/privacy; 15) interactive; 16) strong user control capabilities; 17) readability; 18) efficiency; 19) scannability; and 20) learnability. However, out of the 20 design elements, seven were most often discussed in relation to user engagement, which is navigation, graphical representation, organization, content utility, purpose, simplicity, and readability.…”
Section: Literature Review and Research Modelmentioning
confidence: 99%
“…We welcome reader input on these directions and resulting new resource needs. Designing features based on user feedback should enhance the usefulness of the framework and its website (48,49).…”
Section: Future Directionsmentioning
confidence: 99%
“…The complex art of persuasion calls for a blend of different strategies, including the need for a straightforward presentation of the "what", "how", "where", "when" and "who" complemented with stories. Colour and graphics also help to increase the impact of key points (24).…”
Section: Consider Developing An Attractive Easily Searchable Online mentioning
confidence: 99%